Editorial (2021)
This issue of the journal Cuadernos de Filosofía Latinoamericana comprises ten varied contributions, related to the specific focus of the journal, oriented to the development of Latin American philosophy, and the contributions of other central themes such as universal philosophy, literature and dialogues between philosophy and other sciences. In the last five years, 60% of the articles published in the journal have corresponded to topics related to Latin American philosophy, but the journal has also had an open and plural approach, and has included other topics. Through the coherence with its thematic focus, sustained for forty-one years, and thanks to the opening of other central themes, the journal has strengthened its recognition and impact in Latin America. In the last five years, the citation index of the journal's articles, analyzed by Google Scholar (H5), has increased by 53.3%, and the journal is, currently, in quartile 2, among humanities journals in Colombia. This has allowed it to be indexed in Publindex, the index of the Colombian Ministry of Science and Technology, and to maintain its indexing in other important indexes.